Hubungan Status Gizi, Aktivitas Fisik, Konsumsi Buah Dan Sayur Dengan Kejadian Hipertensi Di Poliklinik Penyakit Dalam RSD Idaman Kota Banjarbaru - Nany Suryani; Noviana Noviana; Oklivia Libri (Jurnal Kesehatan Indonesia, 2020)
Hypertension is a matter of public health, hypertension is the cause of the highest death or called the silent Killer, because hypertension is a hidden killer. A person is said to be hypertension if systolic blood pressure is more than 140 mmHg and diastolic more than 90 mmHg. Some risk factors are thought to have a role in the occurrence of hypertension such as diet, nutritional status and physical activity. This research aims to determine the relationship of nutritional status, physical activity, consumption of fruits and vegetables with the incidence of hypertension. Type of analytical survey research with cross sectional research draft, purposive sampling method with sample of 63 respondents. The results of the study gained the proportion of respondents who had hypertension of 81.0%. Bivariate Analysis uses test rank of Spearman and multivariate analysis with multiple logistics regression. Results of bivariate analysis indicates there is a link between fruit and vegetable consumption (p = 0,000) nutrient status (P = 0,002) and physical activity (p = 0.001) with the incidence of hypertension. Multivariate analysis shows physical activity (P Value = 0.036) (OR = 6.234) as the risk factor most closely related to the incidence of hypertension. To reduce the incidence of hypertension, people are expected to always control blood pressure and avoid the factors that cause hypertensive disease.